1999
DOI: 10.1046/j.1365-2370.1999.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of platelet‐specific alloantigen systems 1–5 in three distinct ethnic groups in Brazil

Abstract: The human platelet antigen (HPA) systems are related to immune platelet disorders as well as to the development of occlusive vascular disease. Several distinct biallelic HPA systems are known, and a heterogeneous distribution of HPA alleles has been described among distinct ethnic groups. In this study we genotyped 320 carefully selected individuals from three distinct ethnic groups in Brazil (Caucasians, Blacks and Amazonian Indians) for the HPA-1, -2, -3, -4 and -5 systems. A similar prevalence for all HPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 48 publications
12
47
8
Order By: Relevance
“…However, the prevalence of VNTR alleles differs between Indigenous and the Oriental populations. Notably is the absence of the largest VNTR, the A allele, which is present in 8-15% of Oriental population [7,24,32]. The distinct prevalence of these alleles among Indigenous population in this study may be influenced by genetic drift or regionspecific selection pressure and importantly, by the high rate of consanguineous marriage [40].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the prevalence of VNTR alleles differs between Indigenous and the Oriental populations. Notably is the absence of the largest VNTR, the A allele, which is present in 8-15% of Oriental population [7,24,32]. The distinct prevalence of these alleles among Indigenous population in this study may be influenced by genetic drift or regionspecific selection pressure and importantly, by the high rate of consanguineous marriage [40].…”
Section: Discussionmentioning
confidence: 75%
“…The characterization of the HPA-2 alleles was performed as reported by Castro et al [32]. Following digestion of the PCR products with BsaHI in the presence of HPA-2a, three fragments of 61, 116, and 242 bp were obtained, whereas in the presence of HPA-2b allele, only two fragments (61 and 358 bp) were observed.…”
Section: Genotyping For Hpa-2mentioning
confidence: 99%
See 1 more Smart Citation
“…The Brazilian population is highly heterogeneous and admixed, presenting important differences in genomic ancestry among regions [9,31]. Studies carried out in Brazilian populations have demonstrated the existence of significant differences in the distribution of HPA antigens throughout the Brazilian territory [10,25], which could generate regional differences in the risk of HPA alloimmunization and its consequences. In the present study, we investigated the variation of HPA frequencies in different Brazilian populations, compared with other world populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HPA frequencies in Brazil have proposed the occurrence of heterogeneity across the Brazilian population produced by the different degrees of admixture throughout the country, suggesting the importance of the formation of HPA panels composed of regional blood donors [10,11]. …”
Section: Introductionmentioning
confidence: 99%